Synthesis and tuning the electro-magnetic properties of Co-Cr substituted Sr-hexaferrite towards diverse usages - Gupta A.; Roy P.K. (My University, 2025)
Strontium hexaferrite is one of the powerful commercial magnets due to its unique characteristic combination of physical, magnetic, and dielectric properties. According to the necessity, their magnetism may be altered as either hard or soft by substitutional effectiveness of the transition elements and optimization of processing parameters. Here, SrFe12-(x+y)CoxCryO19 (x,y = 0,0; 0,1; 0.25,0.75; 0.50,0.50; 0.75,0.25; 1,0) nano ferrites have been successfully synthesized by the sol–gel self-propagation process and the impacts of Co-Cr on the microstructure, densification, magnetic, dielectric, and electrical properties have been analyzed. The XRD data discloses the crystalline ferrite phase with a hexagonal structure (P63/mmc). It is found that the magnetic properties can be tuned up effectively by the substitutions. The samples show a range (0.02–0.48) of the squareness (Mr/Ms) ratio suitable for diverse industrial applications. SrFe11CrO19 composition reveals magnetic improvement in Ms (60 emu/g) and Hc (6.3 kOe) along with decent energy product, i.e., 27.17 MGOe, optimized to approach for a permanent magnet. SrFe11Co0.75Cr0.25O19 & SrFe11CoO19 compositions show a great dilution in hard magnetism having Ms of 71 emu/g along with Hc of 36.21 Oe and 3.23 Oe, respectively. It has opened up the opportunity of possible emersion of the hard magnet in the magnetic recording media application. The proposed work is expected to offer a good notion to modify strontium hexaferrite in order to expand its application areas. © 2020 Elsevier B.V.